Kewajiban Belajar Mengajar Dalam Islam Untuk Meningkatkan Iman Dan Takwa - Wismanto Wismanto; Rahma Tilla Indah; Yolanda Maya Sari; Salsabila Almahda; Masidayu Masidayu (IHSANIKA : Jurnal Pendidikan Agama Islam, 2024)
Teaching and learning is a form of activity that needs to continue to be developed in order to increase human resources through education. Education can take place when someone is an educator and is also being educated, then this process can be called a learning and teaching activity. Learning to teach, including the obligation of every individual, as the Prophet Muhammad, has taught us his people to always continue learning throughout life. The aim of the research is to explain the obligations of teaching and learning in Islam to improve the quality of faith and piety. The method used in this research is a qualitative method with a library method approach, the study materials used as reference sources are magazines, books and the latest journal articles related to the research theme. The results of this research show that it is very important to study in Islam, in fact Islam explains that not only is studying knowledge obligatory but teaching knowledge is also obligatory, and people who teach knowledge (especially religious knowledge) have a very noble position in the sight of Allah Subhanahu Wa Exalted.